The price of politics - Woodward, Bob (Simon & Schuster, 2012)
This book examines the struggle between President Obama and the United States Congress to manage federal spending and tax policy for the three and one half years between 2009 and the summer of 2012. More than half the book focuses on the intense 44-day crisis in June and July 2011 when the United States came to the brink of a potentially catastrophic default on its debt. Based on eighteen months of reporting, the author presents a well-documented examination of how President Obama and the highest profile Republican and Democratic leaders in the U.S. Congress attempted to restore the American economy and improve the federal government's fiscal condition over three and a half years. Providing verbatim, day-by-day accounts, he shows what really happened, what drove the debates and struggles that continue to define the American future.